2007
DOI: 10.1002/ijc.23239
|View full text |Cite
|
Sign up to set email alerts
|

Differential sensitivity of human colon cancer cell lines to the nucleoside analogs ARC and DRB

Abstract: Recently, we identified a nucleoside analog named ARC (4-amino-6-hydrazino-7-b-D-ribofuranosyl-7H-Pyrrolo[2,3-d]pyrimidine-5-carboxamide), which has the properties of a general transcriptional inhibitor. Here, we report the characterization of ARC on a panel of colorectal cancer (CRC) cell lines. Cell death induced by ARC in CRC cells was accompanied by caspase-3 cleavage and correlated with the downregulation of antiapoptotic proteins, survivin and Mcl-1 and with the inhibition of Akt phosphorylation. At the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 17 publications
(35 reference statements)
4
16
0
Order By: Relevance
“…The mechanism whereby clofarabine-bortezomib treatment reduces survivin levels in HCT-116 xenografts could be either p53-dependent (41), as indicated by our Western blot analysis (Supplementary Fig. S1E), or p53-independent (42). Regardless, the greater-than-single-agent activity of this combination has some precedent; previous in vitro experiments have demonstrated that bortezomib-induced cytotoxicity and pro-apoptotic signaling are enhanced by purine nucleoside analogs (43).…”
Section: Discussionmentioning
confidence: 82%
“…The mechanism whereby clofarabine-bortezomib treatment reduces survivin levels in HCT-116 xenografts could be either p53-dependent (41), as indicated by our Western blot analysis (Supplementary Fig. S1E), or p53-independent (42). Regardless, the greater-than-single-agent activity of this combination has some precedent; previous in vitro experiments have demonstrated that bortezomib-induced cytotoxicity and pro-apoptotic signaling are enhanced by purine nucleoside analogs (43).…”
Section: Discussionmentioning
confidence: 82%
“…Similarly, the altered expression of anti-apoptotic Bcl-2 family proteins can confer the tumor cells with TRAIL resistance [12], [21], [24], [44], [45], [46], [61], [62], [63]. It has also been shown that anti-apoptotic protein survivin is highly expressed in colon carcinoma cells [64], [65]. These observations suggest that TRAIL resistance mechanisms might be tumor type and stage-dependent.…”
Section: Discussionmentioning
confidence: 96%
“…In myeloma cells, while RGB 286638 clearly depleted Pol II CTD Ser2 phosphorylation, cytotoxicity was associated with both CDK-dependent and -independent inhibition [86]. The compound ARC [4-amino-6-hydrazino-7-β- D -ribofuranosyl-7H-pyrrolo(2,3-d)-pyrimidine-5-carboxamide; Figure 4(i)] has been shown to induce apoptosis in several types of cancer cells due to its depletion of anti-apoptotic proteins such as MCL-1 and survivin [40,41,108-110]. Using purified P-TEFb in an in vitro kinase assay on a recombinant Pol II CTD, ARC was shown to inhibit this kinase [41].…”
Section: Therapeutic Inhibitors Of Mrna Synthesismentioning
confidence: 99%